Perilaku Konsumsi Mie Instan Mahasiswa Fakultas Ilmu Kesehatan Universitas Muhammadiyah dan Jurusan Gizi Poltekkes Kemenkes Pontianak - Rochmawati Rochmawati; Marlenywati Marlenywati (Poltekkes Kemenkes Pontianak, 2015)
Abstract: Instant Noodle Consumption Behavior Among Students Of Health Sciences Faculty Of Muhammadiyah University Pontianak And Nutrition Department Of Health Polytechnic Of Health Ministry Pontianak. This study aimed at determining the factors associated with instant noodle consumption behaviour among students of Health Sciences Faculty of Muhammadiyah University of Pontianak and Nutrition Department of Health Polytechnic of Health Ministry of Pontianak. Using cross-sectional design, this study employed 145 students as the samples and were selected by using simple random sampling. The statistical test used was chi-square test. The study revealed that there were no significant correlation ofÂ nutritional knowledge (p = 1.000, PR = 1.004 with 95% CI = 0.712 to 1.415), food safety(p = 0.064, PR =0,646with 95% CI = 0.407 to 1.025), media exposure (p = 0.139, PR = 1.419 with 95% CI = 0.911 to 2.211), inhabitancy (p = 0.851, PR = 0.932 with 95% CI = 0.646 to 1.344) and instant noodles consumption behavior among students of Health Sciences Faculty of Muhammadiyah University Pontianak and Nutrition Department of Health Polytechnic of Health Ministry Pontianak.Abstrak : Perilaku Konsumsi Mie Instan Mahasiswa Fakultas Ilmu Kesehatan Universitas Muhammadiyah Dan Jurusan Gizi Poltekkes Kemenkes Pontianak. Tujuan penelitian yaitu untuk mengetahui faktor-faktor yang berhubungan dengan perilaku konsumsi mie instan pada mahasiswaÂ Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak dan Jurusan Gizi Poltekkes Kemenkes Pontianak. Jumlah sampel yaitu 145 orang dengan penentuan sampel secara Simple random sampling dan menggunakan desain penelitian cross sectional. Uji statistik yang digunakan adalah Chi-square. Hasil penelitian menunjukkan tidak terdapat hubungan yang bermakna antara pengetahuan gizi (p = 1,000, PR = 1,004 dengan CI 95% = 0,712-1,415), keamanan pangan (p = 0,064, PR = 0,646 dengan CI 95% =0,407-1,025), keterpaparan media (p = 0,139, PR = 1,419 dengan CI 95% = 0,911-2,211), dan tempat tinggal (p = 0,851, PR = 0,932 dengan CI 95% = 0,646-1,344) dengan perilaku konsumsi mie instan pada mahasiswa Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak dan Poltekkes Kemenkes Pontianak.